Presença de arsênio no solo, pastagem e equinos no manejo de Urochloa decumbens com herbicida MSMA - Duarte, Mario (Universidade Federal de São Carlos, 2025)
Brazil has the third-largest horse population (Equus caballus) in the world, with approximately 5.8 million animals. The diet of these horses is predominantly composed of subtropical grasses, particularly cultivars of the Cynodon genus, with “Coastcross-1” being the most popular. However, pastures are often infested by the invasive plant Brachiaria decumbens (Urochloa decumbens), which horses tend to avoid during grazing, contributing to pasture degradation. A practical and effective strategy for controlling invasive plants, especially Brachiaria, is the use of selective herbicides. The herbicide MSMA (monosodium methylarsonate) is widely used to control invasive plants in sugarcane fields. Although MSMA is not officially recommended for use in pastures, it is frequently employed to control Brachiaria in grazing areas and hay production systems. MSMA is an organoarsenic herbicide with a mechanism of action that is not yet fully understood. It is classified as moderately toxic (Category III) and hazardous to the environment (Environmental Risk Class III). Once applied, MSMA degrades into four arsenic species with varying degrees of toxicity: arsenite, arsenate, monomethylarsonic acid, and dimethylarsinic acid. MSMA has the potential to introduce arsenic into the soil and plants. The toxicity of arsenic is primarily due to its ability to inhibit cellular metabolism, compromising the synthesis of adenosine triphosphate (ATP), in addition to its carcinogenic and teratogenic properties. The hypothesis of this thesis is that the use of an organoarsenic herbicide in pasture contaminates the soil, plants, and animals with the element arsenic. The objective was to determine whether the application of this herbicide was a determining factor in increasing arsenic levels in the environment and in horses. Two areas of 25,000 m² each were studied (one treated with MSMA and one control), along with 16 horses—8 grazed in the MSMA area and 8 in the control area. The MSMA dose applied was 3.59 kg/ha. Samples of soil, roots, and aerial parts of Brachiaria and Coastcross-1 were collected, as well as blood, urine, and hair samples from the animals. The results from the MSMA-treated area showed higher arsenic accumulation in Brachiaria (26.20 ppm ± 0.08) compared to Coastcross (12.66 ppm ± 2.94), with statistical significance (p<0.0001). Brachiaria accumulated 10.69 ppm (± 1.69) in the MSMA area versus 6.06 ppm (± 0.96) in the control area (p<0.0001). Coastcross accumulated 10.73 ppm (± 1.22) in the MSMA area versus 1.6 ppm (± 0.41) in the control area (p<0.0001). Soil samples did not show detectable levels of arsenic. Horses grazing in MSMA-treated pastures (MSMA group) exhibited higher arsenic levels in blood (1.67 ppm ± 0.047) compared to the control group (1.35 ppm ± 0.0531) (p<0.05). In urine, arsenic levels were 1.62 ppm (± 0.189) in the MSMA group versus 1.195 ppm (± 0.111) in the control group (p<0.05). No significant differences were observed in arsenic levels in the hair between treated and control animals. The results demonstrate that the use of MSMA herbicide in pastures promotes significant arsenic accumulation in forage plants and in the horses that consume them, posing a potential risk to animal health and food safety.
Presence of arsenic in soil, pasture, and horses under the management of Urochloa decumbens with MSMA herbicide
Keywords: Arsênio; Cavalo; Coast-cross; Intoxicação; Braquiária; Arsenic; Horse; Intoxication; Braquiaria; CIENCIAS AGRARIAS::MEDICINA VETERINARIA